2005
DOI: 10.1128/aem.71.12.7806-7818.2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Isolation of Ultrasmall Microorganisms from a 120,000-Year-Old Greenland Glacier Ice Core

Abstract: The abundant microbial population in a 3,043-m-deep Greenland glacier ice core was dominated by ultrasmall cells (<0.1 m 3 ) that may represent intrinsically small organisms or starved, minute forms of normalsized microbes. In order to examine their diversity and obtain isolates, we enriched for ultrasmall psychrophiles by filtering melted ice through filters with different pore sizes, inoculating anaerobic low-nutrient liquid media, and performing successive rounds of filtrations and recultivations at 5°C. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(119 citation statements)
references
References 36 publications
4
113
1
1
Order By: Relevance
“…Miteva and Brenchley (2005) and Tung et al (2005Tung et al ( , 2006 found from Scanning Electron Microscopy that bacteria in GISP2 ice have sizes typically 0.2 to 0.5 µm, and Priscu (private communication, 2007) found from flow cytometry that, in the WAIS Divide ice core, both biotic particles (those containing DNA that stains with a dye such as Syto 60) and abiotic particles have sizes peaked at 0.3 µm. By contrast, studies of aerosol fluorescence spectra have generally been made on concentrates of atmospheric and marine aerosols (Yamashita and Tanoue, 2003;Coble, 1996) rather sharp emission peak at 353 nm, whereas the emission peak for protein-bound Trp is ∼330 nm, the downshift being the result of binding into proteins.…”
Section: Deep Cores In Central Greenlandmentioning
confidence: 99%
“…Miteva and Brenchley (2005) and Tung et al (2005Tung et al ( , 2006 found from Scanning Electron Microscopy that bacteria in GISP2 ice have sizes typically 0.2 to 0.5 µm, and Priscu (private communication, 2007) found from flow cytometry that, in the WAIS Divide ice core, both biotic particles (those containing DNA that stains with a dye such as Syto 60) and abiotic particles have sizes peaked at 0.3 µm. By contrast, studies of aerosol fluorescence spectra have generally been made on concentrates of atmospheric and marine aerosols (Yamashita and Tanoue, 2003;Coble, 1996) rather sharp emission peak at 353 nm, whereas the emission peak for protein-bound Trp is ∼330 nm, the downshift being the result of binding into proteins.…”
Section: Deep Cores In Central Greenlandmentioning
confidence: 99%
“…Over 10% of viable bacterial spores were enumerated in GISP2 ice (Yung et al 2007). Systematic studies of 3043-m-deep silty GISP2 ice detected an abundant and diverse microbial population and recovered isolates including ultrasmall and novel microorganisms (Sheridan et al 2003;Miteva et al 2004;Miteva & Brenchley 2005;LovelandCurtze et al 2008LovelandCurtze et al , 2010. Similar viable microbial populations were found in the basal ice of other Greenland glaciers (Yde et al 2010;Stibal et al 2012).…”
mentioning
confidence: 99%
“…Sheridan et al (2003) found 6.1 x 10 7 and 9.1 x 10 7 cells ml -1 in two duplicate samples, while Tung et al (2006) counted about 10 11 cells g -1 of sediment. Isolated anaerobic and aerobic enrichment culture studies show a diverse community represented by several major phylogenetic groups: Ǐ-, ǐ-and Ǒ-Proteobacteria, Thermus-Deinococcus, Bacteroides, Eubacterium, Clostridium, Fusobacterium and Actinobacteria (Sheridan et al, 2003;Miteva et al, 2004;Miteva and Brenchley, 2005). The CH 4 concentration in basal ice at GRIP and GISP2 ice cores is much higher (6,000 and 12,000 ppm, respectively) than atmospheric concentrations (1.8 ppm) (Tison et al, 1998;Price and Sowers, 2004), and Tung et al (2005Tung et al ( , 2006 have detected methanogens that are likely to be responsible for producing excess CH 4 concentrations.…”
Section: Greenlandmentioning
confidence: 99%